Computer tomography scanning of Homo Erectus crania Ngandong 7 from Java: Internal structure, paleopathology and post-mortem history - Antoine Balzeau, Antoine Balzeau (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Computer Tomography scanning has recently been a tool for diagnosis of normal anatomy and pathology in medical sciences. The CT method has also been applied in ancient human skeletal remains and yield good results for researching the morphology, pathology, and postfossilization bone alteration. Paleoanthropological evidences exhibit that biological remains sometimes are fossilised, thus enabling the pursuit of scientific inquiries in regard to anatomy and biology of ancient humans.Aim of study: to know the morphology and anatomy of the crania including the internal structures that is not feasible in external bone study, such air pneumatisation, the shape of frontal sinuses, and thickness of the external table, diploe, or the internal table. This study also aims to know the mineralization distribution as a result of fossilization.Material and Method: The material in this study was a fossil crania of Ngandong 7 that belongs to the latest representation of the Homo erectus from Ngandong, East Java, Indonesia. Ng 7 is from the Late Pleistocene period dated about 27,000 to 100,000 years ago. The CT scan was conducted in the QuinzeVingts hospital, Paris, in January 2001. The method used is by applying a medical CT-based data in order to extract the maximum information concerning mineralization, internal cranial features, osseous distribution and disease. An adapted acquisition and analysis protocols are developed from the CT scan.Results: Mineralization of Ng 7 occurred during fossilization, causing the diploe to be thickened than normally in antemortem and prefosilization periods. Because of post-mortem transformation of the individual structures, many slices of CT scans were necessary. The internal structures showed ovoid shape of frontal sinuses, and well developed pneumatisation of the mastoid region. Cracks were detected as a result of postfosilization compressions. Lesions appeared on CT scan just posterior to the bregma in the form of eroded external table. This caused diffuse boundary between external table, diploe, and internal table due to homogenous mineralizationConclusion: It is concluded that the Ngandong 7 Homo erectus shares internal morphological similarities with other Ngandong and Sambungmacan fossils and presents lesions that might have caused by pathology during the life of the individual. The post-mortem history of this fossil appears to be composed of at least two distinct stages with osseous loss and fluvial transport, followed by taphonomic and diagenetic processes.Key words: Ngandong, Homo erectus, computer tomography, paleopathology, post-mortem history